The Diversity of the CRISPR-Cas System and Prophages Present in the Genome Reveals the Co-evolution of Bifidobacterium pseudocatenulatum and Phages - Wang, Gang; Liu, Qian; Pei, Zhangming; Wang, Linlin; Tian, Peijun; Liu, Zhenmin; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Frontiers in Microbiology, 2020)
Diverse CRISPR-Cas systems constitute an indispensable part of the bacterial adaptive immune system against viral infections. However, to escape from this immune system, bacteriophages have also evolved corresponding anti-defence measures. We investigated the diversity of CRISRP-Cas systems and the presence of prophages in the genomes of 66 Bifidobacterium pseudocatenulatum strains. Our findings revealed a high occurrence of complete CRISPR-Cas systems (62%, 41/66) in the B. pseudocatenulatum genomes. Subtypes I-C, I-U and II-A, were found to be widespread in this species. No significant association was found between the number of bacterial CRISPR spacers and its host’s age. This study on prophages within B. pseudocatenulatum genomes revealed that prophage genes related to distinct functional modules became degrade at different levels, indicating that these prophages were not likely to enter lytic cycle spontaneously. Further, the evolutionary analysis of prophages in this study revealed that they might be derived from different phage ancestors. Notably, self-targeting phenomenon within B. pseudocatenulatum and Anti-CRISPR (Acr) coding genes in prophages was observed. Taken together, our results indicate that the competition between B. pseudocatenulatum and phages is a major driving factor for the genomic diversity of both partners.